A Masculinity of Gender Stereotypes in Brave Motion Picture - Dharpa Sugianto, Tirta Agraprana; Probowati, Yeni; Setyowati, Yulis (EL2J (English Language and Literature Journal), 2024)
Movies are a potent medium for learning, as they are not only accessible but also have the capability to shape behaviour and provoke meaningful conversations. It is crucial to recognize that not all cinematic content promotes positive examples; some scenes reinforce negative portrayals and harmful stereotypes. This study decisively examines the gender dynamics in the Walt Disney Company film "Brave," which exemplifies the persistent issue of gender stereotypes in media. The primary objective of this research is to assertively analyse the gender roles depicted in children's films, with a particular focus on Merida’s character in "Brave." A qualitative research approach is adopted, employing a thorough methodology that includes multiple viewings of the film, detailed summary readings, extensive note-taking, script interpretation, identification of key terms and dialogues, and review of pertinent academic journals and articles online. This study delves into the gender dynamics presented in the Walt Disney Company’s animated film "Brave," which serves as a compelling example of the lingering issue of gender stereotypes in media. The primary goal of this research is to critically assess the gender roles depicted in children's films, with a particular emphasis on the character of Merida in "Brave." It seeks to understand how Merida challenges traditional gender expectations and whether she ultimately conforms to established gender norms. The research questions are designed to scrutinize the characteristics of Princess Merida. The findings reveal that Merida embodies ten distinct masculine traits, illustrating her complexity as a character who defies conventional expectations of femininity.